Analisis Perilaku Pengguna Website Sistem Informasi Akademik Universitas Veteran Bangun Nusantara Sukoharjo Menggunakan Technology Acceptance Model (TAM) - Asep Permadi; Tri Irawati; Bebas Widada (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2024)
UNIVET BANTARA Sukoharjo has implemented a website which includes an academic information system. With this academic information system, it is intended that students can access information online anytime and anywhere. The website-based academic information system implemented by UNIVET BANTARA has undergone an update in 2019. So by updating the academic information system since 2019, it is hoped that students will feel comfortable in using the new system. Based on these problems, it is necessary to analyze the behavior of users of the new academic information system using the Technology Acceptance Model (TAM). The purpose of this study is to analyze the behavior of website users at Univet Bantara Sukoharjo by using the technology acceptance model method. In analyzing the data, the author uses Partial Least Squares (PLS) analysis, and the author develops an application to test the technology acceptance model method with the PHP programming language. The results showed that five of the six proposed hypotheses had a significant positive effect on the dependent variable with an effect value of 0,653 (65,3%), 0,447 (44,7%), 0,677 (67,7%), 0,520 (52,0%), 0,605 (60,5%) and one hypothesis had a significant negative effect on the value of 0,170 (17,0%)